TRANSCATHETER TRICUSPID INTERVENTION: SHORT PERSPECTIVE - Sidhi Laksono; Yoseph Alam Naibaho (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2024)
Introduction Around 4% of individuals who are 75 years old or older demonstrate clinically significant tricuspid regurgitation (TR). Primary tricuspid regurgitation is caused by a structural abnormality of the tricuspid valve and is present in 8-10% of patients with tricuspid valve issues. Secondary tricuspid regurgitation is frequently seen due to annular stretching resulting from right ventricular enlargement and dysfunction due to pulmonary hypertension, which is commonly associated with left-sided heart disease or atrial fibrillation. Regardless of its cause, TR results in excessive volume and heightened wall pressure, which contribute negatively to harmful remodeling and worsening of TR. Interventions to address TR are not being used enough in daily clinical practice due to higher surgical risk and patients presenting late. An extensive electronic search was performed using PubMed, Google Scholar, and ScienceDirect. The inquiry was confined to English-language publications. A manual search of relevant publications and reference lists was conducted.. Result The newly introduced transcatheter tricuspid valve interventions are designed to meet this unfulfilled requirement. Furthermore, a comprehensive evaluation of the currently available transcatheter treatments, including the primary factors for choosing patients and devices, as well as details on lingering uncertainties, is presented Discussion Both dedicated expertise and a comprehensive evaluation by a multidisciplinary Heart Team are crucial in effectively incorporating these new techniques and choosing suitable patients—an established method to assess patients with TR who are potential candidates for transcatheter procedures.